The Political Effects of the Russian–Ukrainian War on International Trade - Akpomedaye, Jerry; Orhero, A. E. (PERSPEKTIF, 2025)
The Russian-Ukrainian war has profoundly impacted international Trade, reshaping global economic dynamics. This study explores the political effects of the conflict, focusing on economic sanctions, trade realignments, and disrupted supply chains. As significant energy and essential commodities exporters, Russia and Ukraine's roles in global Trade have been pivotal. Hostilities have caused inflation, food insecurity, and a reevaluation of global economic dependencies. Anchored in the Geoeconomic Power Theory, the study uses historical and content analysis to examine documented data. Key findings reveal disruptions in supply chains, rising commodity prices, changes in trade relationships, and significant impacts on energy and agricultural markets. Sanctions have reconfigured trade partnerships, fostered covert economies, and influenced long-term trade policies, including shifts toward regionalization, economic blocs, and alternative financial systems. The study underscores the strategic use of economic tools in geopolitics and recommends real-time trade monitoring systems to track and respond to global trade fluctuations caused by the war, ensuring businesses adapt to emerging trends effectively.